Two spectrophotometric methods for simultaneous determination of some antihyperlipidemic drugs - Nada S. Abdelwahab; Badr A. El-Zeiny; Salwa I. Tohamy (Elsevier, 2012)
Two simple, accurate, precise and economic spectrophotometric methods have been developed for simultaneous determination of Atorvastatin calcium (ATR) and Ezetimibe (EZ) in their bulk powder and pharmaceutical dosage form. Method (I) is based on dual wavelength analysis while method (II) is the mean centering of ratio spectra spectrophotometric (MCR) method. In method (I), two wavelengths were selected for each drug in such a way that the difference in absorbance was zero for the second drug. At wavelengths 226.6 and 244Â nm EZ had equal absorbance values; therefore, these two wavelengths have been used to determine ATR; on a similar basis 228.6 and 262.8Â nm were selected to determine EZ in their binary mixtures. In method II, the absorption spectra of both ATR and EZ with different concentrations were recorded over the range 200â350, divided by the spectrum of suitable divisor of both ATR and EZ and then the obtained ratio spectra were mean centered. The concentrations of active components were then determined from the calibration graphs obtained by measuring the amplitudes at 215â260Â nm (peak to peak) for both ATR and EZ. Accuracy and precision of the developed methods have been tested; in addition recovery studies have been carried out in order to confirm their accuracy. On the other hand, selectivities of the methods were tested by application for determination of different synthetic mixtures containing different ratios of the studied drugs. The developed methods have been successfully used for determination of ATR and EZ in their combined dosage form and statistical comparison of the developed methods with the reported spectrophotometric one using F and Student's t-tests showed no significant difference regarding both accuracy and precision. Keywords: Atorvastatin, Ezetimibe, Dual wavelength method, Mean centering of ratio spectra, Spectrophotometry